2015
DOI: 10.1039/c4ra10842f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo synergistic interaction of substituted chalcone derivatives with norfloxacin against methicillin resistant Staphylococcus aureus

Abstract: The present investigation shows that certain substituted chalcone derivatives diminish the escalation of bacterial cellsviainhibiting bacterial efflux pump and exhibit a synergistic interaction with norfloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…43,61 Compounds 6a, 6c, 6d, and 6f, with LC 50 values of 8.03, 6.66, 9.09, and 10.80 mg L −1 , respectively, and LC 90 values of 11.9, 9.97, 13.58, and 18.21 mg L −1 , respectively, fall in this category. Analysis of structure-activity relationships has guided the synthesis of substituted chalcone derivatives to obtain molecules with other biological properties, such as antimicrobials, 62 compounds for immunodiagnosis of Parkinson's disease, 63 and antioxidants. 64 The presence of a free hydroxyl group in the aromatic ring of chalcones increases the A-ring lipophilicity 64 and is an important structural feature for the antimicrobial activity against methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…43,61 Compounds 6a, 6c, 6d, and 6f, with LC 50 values of 8.03, 6.66, 9.09, and 10.80 mg L −1 , respectively, and LC 90 values of 11.9, 9.97, 13.58, and 18.21 mg L −1 , respectively, fall in this category. Analysis of structure-activity relationships has guided the synthesis of substituted chalcone derivatives to obtain molecules with other biological properties, such as antimicrobials, 62 compounds for immunodiagnosis of Parkinson's disease, 63 and antioxidants. 64 The presence of a free hydroxyl group in the aromatic ring of chalcones increases the A-ring lipophilicity 64 and is an important structural feature for the antimicrobial activity against methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the modification of naringenin with O -alkyl chains, the incorporation of an oxime group was observed to significantly increase its biological activity. In many cases, the replacement of the carbonyl group with an oxime at the C-4 position resulted in higher antibacterial [ 20 ] and cytotoxic activities [ 21 ]. The modification of naringenin to its oxime enhanced its antitumor activity against rat pheochromocytoma (PC-12), human colon (HT-29) and breast (MCF-7) cancer cell lines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indole–chalcone hybrids 47a , b (MIC: 12.5–100 µM) showed a considerable activity against 10 MRSA clinical isolates, including MRSA ST‐1745, MRSA ST‐2071, MRSA ST‐2438, MRSA ST‐8029, MRSA ST‐5457, MRSA ST‐10342, MRSA ST‐10760, MRSA ST‐3151, and MRSA P‐6642, and the SAR demonstrated that the electron‐donating group on the phenyl ring increased the activity, whereas the electron‐withdrawing group decreased the activity. [ 79 ] Hybrid 47a (MIC: 12.5–50 µM), which was found to be 5‐ to 40‐fold more potent than the reference norfloxacin (MIC: 125–500 µM) against 10 MRSA clinical isolates, also exhibited a synergistic effect with norfloxacin, as the combination of this hybrid with norfloxacin led to a 2‐ to 16‐fold reduction in MIC values of norfloxacin against the tested MRSA isolates. The mechanistic study proved that hybrid 47a could exert the antibacterial activity through blocking multidrug‐resistant efflux pump.…”
Section: Indole Hybridsmentioning
confidence: 99%
“…[78] The indole-chalcone hybrids 47a,b (MIC: 12. and MRSA P-6642, and the SAR demonstrated that the electrondonating group on the phenyl ring increased the activity, whereas the electron-withdrawing group decreased the activity. [79] Hybrid 47a but also demonstrated a potential inhibitory activity (IC 50 : 355 and 24 nM) against MRSA PK. [80] The SAR revealed that 2-hydroxyl-5bromophenyl group was crucial for the high activity, and replacement of this fragment by the second indole moiety reduced the activity; the substituent at the C-6 position also had great influence on the activity, and the bromo group was beneficial for the activity.…”
Section: Indole Hybridsmentioning
confidence: 99%